The Influence of CapCut-Based Interactive Video Media on Islamic Religious Education Learning Outcomes in Elementary Schools - Windhari B, Putri; Nurhayati, Nurhayati; Akbar, Muhammad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to determine the effect of using interactive learning media based on the CapCut application on the learning outcomes of Islamic Religious Education (PAI) of sixth-grade students at SD Negeri 1 Laloeha. This study uses a quantitative approach with an experimental method and a one-group pretest–posttest design. The research subjects were 30 students, all of whom were sampled through a saturated sampling technique. Data collection was carried out through learning outcome tests (pretest and posttest), student response questionnaires, observations, and interviews. Data were analyzed using descriptive statistics, Paired Sample t-Test, and N-Gain test. The results showed that the average value of student learning outcomes increased from 68.40 in the pretest to 89.20 in the posttest. The t-test results showed a significance value of 0.000 (p <0.05), which means there was a significant difference between learning outcomes before and after the use of CapCut-based learning media. The N-Gain test showed that 66.7% of students were in the great improvement category, 30% in the medium category, and 3.3% in the low category. Furthermore, the questionnaire results showed that students responded very positively to the use of CapCut, particularly in increasing motivation, understanding the material, and creating a pleasant learning environment.